How canopy structural and morphological characteristics, and forage chemical composition affect a pasture-based dairy system? - de Paula Rezende, Cláudia; Pereira, José Marques; Magalhães, Albertí Ferreira; Ferreira, Igor Machado [UNESP]; Homem, Bruno Grossi Costa; Casagrande, Daniel Rume (Universidade Estadual de Londrina, 2021)
Pasture-based systems are prevalent among small-scale family farms. Many farmers consider that the nutritional value of the plant is more relevant than the canopy structure. This study aimed to analyze the various factors related to plant structure and chemical composition that most influence milk yield per hectare under rotational stocking. The experiment was performed at the Animal Husbandry Experimental Station of the Extreme South of Bahia. Three rotational stocking systems with three forage species [Cynodon dactylon (L.) Pers. cv. Tifton 85, Urochloa brizantha (Hochst. ex A. Rich.) Stapf. cv. Xaraés, and Megathyrsus maximus Jacq. cv. Mombasa] were evaluated. Nine crossbred Holstein x Gyr cows were allocated to a balanced 3 x 3 Latin square design. The cows were rotated in three pastures every 14 days. The experimental period consisted of seven evaluation cycles of 42 days each. Cluster analysis, principal component analysis (PCA), and multivariate linear regression were the statistical techniques used to evaluate plant structure and morphological characteristics, and animal performance. Xaraés palisadegrass and Mombasa Guinea grass were similar for all evaluated characteristics (P > 0.05), whereas Tifton 85 was different from them in terms of structural, morphological, and chemical composition characteristics (P < 0.05). In the PCA, 59.1% of the total variance was explained by components 1 and 2 for the structural and morphological characteristics, and forage chemical composition. Forage structural and morphological variables showed better results in the multivariate linear regression analysis for milk yield per hectare. Structural and morphological characteristics were more correlated with Mombasa Guinea grass than Xaraés palisadegrass and Tifton 85. The structural and morphological characteristics of forages were the main factors determining milk yield per hectare in exclusively pasture-based systems with animals of low production.
Como as características estruturais e morfológicas do dossel, e a composição química da forragem afetam um sistema de produção de leite em pastagem?
Keywords: Cynodon; Forage chemical composition; Grazing management; Megathyrsus; Urochloa